Investigation of right lobe hepatic vein variations of donor using 64-detector computed tomography before living donor liver transplantation - Kalaycı, Tuğçe Özlem; Kutlu, Ramazan; Karasu, Şebnem; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To investigate the anatomy and variations of right lobe accessory veins and segment 5-8 veins draining into middle hepatic vein with 64 slice multidetector computed tomography (CT). Materials and Methods: 100 consecutive living donor candidates underwent 64 slice CT angiography. Image interpretation was performed based on source axial images, multiplanar reformats, and three-dimensional postprocessing images by the same radiologist. Results: Segment 5 and 8 veins with larger diameters were frequently found to be the proximal ones. Accessory hepatic veins were present in the great majority of cases (83%). Most of them were the inferior right hepatic veins (55%). All cases were classified according to the number of segment 5-8 veins and the presence or absence of a right accessory hepatic vein. Most of the donors had more than one segment 5-8 vein and right lobe accessory veins (57%). Conclusion: Multidetector CT is a valuable technique for investigating the venous anatomy of the liver in living donor candidates. Anatomy and variations of the hepatic veins can easily be evaluated by using multiplanar images.